2021
DOI: 10.1093/ejcts/ezab491
|View full text |Cite
|
Sign up to set email alerts
|

Reinterventions and new aortic events after aortic surgery in Marfan syndrome

Abstract: OBJECTIVES Pre-emptive strategies to manage the aortic complications of Marfan syndrome have resulted in improved life expectancy yet, secondary to the variation of phenotypic expression, anticipating the risk and nature of future aortic events is challenging. We examine rates of new aortic events and reinterventions in a Marfan cohort following initial aortic presentation. METHODS Retrospective cohort study of Marfan patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Schoenhoff and colleagues ( 8 ) investigated the fate of untreated distal aortas in 86 MFS patients and found that acute aortic dissection led to an increased requirement for interventions on downstream aortic segments. The same conclusion was reached in other studies ( 9 11 , 21 ). It is not difficult to conclude that the fate of residual aorta in patients with aortic dissection depends on thrombosis of the false lumen and aortic remodelling ( 22 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Schoenhoff and colleagues ( 8 ) investigated the fate of untreated distal aortas in 86 MFS patients and found that acute aortic dissection led to an increased requirement for interventions on downstream aortic segments. The same conclusion was reached in other studies ( 9 11 , 21 ). It is not difficult to conclude that the fate of residual aorta in patients with aortic dissection depends on thrombosis of the false lumen and aortic remodelling ( 22 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, with increasing survival time, descending aortic dilation or primary type B aortic dissection may occur in MFS patients after aortic root surgery (1,5,6). Aortic dissection and previous root replacement have been recognized as potential risk factors for lesions on the distal aorta in MFS (5, [7][8][9][10][11]. Some recent studies have also described aortic aneurysm without dissection and peripheral arterial aneurysms in MFS (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Another important nding, that the study by L. de Beaufort et al report is that patients with MFS who had a rst surgery due to an AAD, more frequently required a reintervention compared to patients without MFS, reporting freedom from reintervention of 44.7% compared to 81.5% (P < 0.001) (26). These results have been supported by another study, that also reports that patients treated for an initial AAD, are more likely to have any reintervention compared to patients who were intervened initially for an aneurysmal degeneration without AAD (P = 0.008) (27). Accounting for all procedures, in our study, we found that 16% of patients required any type of reintervention, with reintervention rates at 1, 2.5, and 5 years of 10%, 14%, and 17%, respectively (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…We further focused on proximal aortic repair as a potential factor influencing incidence of TBAD in MFS. It is unclear whether elective aortic root replacement adds to the risk of TBAD due to increase of wall stiffness or if replacing the aneurysm will stabilize more distal segments of the aorta (27). In our population valve-sparing aortic root replacement compared to a Bentall procedure showed no significant difference in freedom from TBAD.…”
Section: Discussionmentioning
confidence: 64%